The Function of \(β\)-Cyclodextrin (CDs) in the Textile Industry: A Detailed Review - Fabricio Maestá Bezerra; Manuel José Lis; Helen Beraldo Firmino; Joyce Gabriella Dias da Silva; Rita de Cassia Siqueira Curto Valle; José Alexandre Borges Valle; Fabio Alexandre Pereira Scacchetti; André Luiz Tessaro (Chemistry and Biochemistry: Research Progress Vol. 4, 2025)
Since the first publication of cyclodextrins (CDs) in 1891 and the first patent in 1953, many technological advances have occurred, and the application of CDs has expanded. \(β\)-Cyclodextrin (\(β\)-CD) is an oligosaccharide composed of seven units of D-(+)-glucopyranose joined by \(α\)-1,4 bonds, which is obtained from starch. Its singular trunk conical shape organization, with a well-defined cavity, provides an adequate environment for several types of molecules to be included. Complexation changes the properties of the guest molecules and can increase their stability and bioavailability, protecting against degradation, and reducing their volatility. Thanks to its versatility, biocompatibility, and biodegradability, \(β\)-CD is widespread in many research and industrial applications. In this review, the role of \(β\)-CD and its derivatives in the textile industry was summarized. First, some general physicochemical characteristics were presented, followed by their application in the areas of dyeing, finishing, and wastewater treatment. The review covers the role of \(β\)-CD as an auxiliary agent in dyeing, and as a matrix for dye adsorption until chemical modifications are applied as a finishing agent. The study concluded that the increasing use of CDs in the textile industry is the result, among other factors, of the versatility of these cyclic molecules and the benefits of their use across the productive chain of this sector. Their unique ability to form an inclusion complex with a wide variety of molecules allows their use in several sectors. Finally, new perspectives about its use in textiles, such as in smart materials for microbial control, are presented.